Non-Parametric Analysis of Retailer Performance in Selected EU Countries: Assessing the Impact of COVID-19 - Niftiyev , Ibrahim; David, Delia; Pordea , Daniela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
The COVID-19 pandemic had a profound impact on microeconomic realities by creating uncertainty, changing economic conditions and ultimately reducing market activity. These effects were felt at a subsectoral level in a large number of European Union (EU) countries. This paper focuses on Spain, Italy, France, Poland and Romania to comparatively assess the differences at a firm level before and after the occurrence of COVID-19. In this study, a non-parametric approach was used for microdata collected from non-specialized retail firms in the agricultural and chemical sectors using multiple correspondence analysis (MCA) and the Wilcoxon signed rank test. The study analyzed micro and small firms and concluded that across firm size and country, return on capital (ROC) distress—ratio of the coefficient of variation of the post-COVID-19 period to the pre-COVID-19 period—was the highest, especially for Spanish and Italian micro firms and Polish small firms. Working capital distress was similar and affected Spanish, Polish and French small businesses. Asset depreciation problems were greatest for Italian, Spanish and Polish small businesses compared to the others. The results of the Wilcoxon signed rank test showed statistically significant differences in employment and working capital between the pre-and post-pandemic samples. Our results suggest that COVID-19 had a noticeable impact at the firm level in the case countries, which can be assessed using non-parametric methods. Policymakers should constantly evaluate the performance of firms in each sector to develop rigid policy proposals for the potential economic disruptions in our time of multiple crises.